Motivadores de uso de modais de deslocamento feminino associados a economia compartilhada: estudo de caso da plataforma BlaBlaCar “Só Para Elas” - Lasas, Mariana de Fátima Cópola (Universidade Estadual Paulista (Unesp), 2021)
Nowadays, technology is present in practically all daily activities. Applications are constantly appearing that connect people to people and to products or services. In this way, technological resources present numerous possibilities, among them that of facilitating the tourist activity that has increasingly sought to reach a specific consumer niche and which has been entering tourism and in the technological world, which is the female audience. Given this scenario, this research aims to analyze the motivations for the use of tourism service startups of the BlaBlaCar platform “Só Para Elas”, linked to the shared economy and its consumption relationship with the female audience. Field research was used as a methodology with the application of a questionnaire available in the virtual environment with feedback from 63 users of the application. It was possible to verify from the survey results that users are motivated by the feeling of safety in travel, with regard to cases of harassment, as well as the reduction of the travel cost, the practicality, the convenience of schedules and having new experiences.

Na contemporaneidade a tecnologia se faz presente em praticamente todas as atividades cotidianas. Surgem de forma constante aplicativos que interligam pessoas, produtos e serviços. Os recursos tecnológicos apresentam inúmeras possibilidades- dentre elas a de facilitar a atividade turística que tem buscado alcançar cada vez mais um nicho consumidor específico e que vem se inserindo no turismo e no mundo tecnológico que é o público feminino. Diante deste cenário, o presente trabalho tem por objetivo analisar os motivadores de uso da startup de serviços turísticos da plataforma BlaBlaCar “Só Para Elas”, vinculada à economia compartilhada e sua relação de consumo com o público feminino. Utilizou-se como metodologia a aplicação de um questionário via Google Forms, disponibilizado no meio virtual com retorno de 63 usuárias do aplicativo. Foi possível verificar a partir dos resultados obtidos, que as usuárias são motivadas pela sensação de segurança nas viagens, no que tange aos casos de assédio, bem como, a redução do custo da viagem, a praticidade, a comodidade de horários e ter novas experiências.
Motivators for the use of female displacement modes associated with the shared economy: case study of the BlaBlaCar platform “Only For Them”
Keywords: Feminine; Shared economy; Tourism; Feminino; Economia Compartilhada; Turismo; Mulheres no desenvolvimento; Tecnologia e mulheres; Aplicativos móveis; Transportes coletivos